THE INFLUENCE OF GOOD GOVERNANCE PRINCIPLES (TRANSPARENCY, ACCOUNTABILITY, AND PARTICIPATION) ON THE EFFECTIVENESS OF SENIOR HIGH SCHOOL MANAGEMENT: AN EXPLANATORY SEQUENTIAL MIXED METHODS STUDY IN PUBLIC AND PRIVATE SCHOOLS IN EAST KALIMANTAN - Irriyanti; Syaharudin; Warni Juwita; Widyatmike Gede Mulawarman; Mukhamad Nurhadi (RADJA PUBLIKA, 2026)
This study aims to analyze the influence of transparency, accountability, and participation on the effectiveness of school management. The study employed a mixed methods approach with a sequential explanatory design, involving the collection and analysis of quantitative data, followed by qualitative data to deepen the research findings. The sample consisted of 43 respondents, consisting of principals, teachers, and administrative staff from several public and private schools. Data collection techniques included questionnaires, interviews, and documentation. The quantitative analysis showed that transparency, accountability, and participation simultaneously had a significant influence on the effectiveness of school management. However, only participation had a significant effect, while transparency and accountability did not. The coefficient determination test showed that the three variables explained 76.6% of the variation in school management effectiveness. The qualitative analysis revealed that participation was the primary factor influencing the effectiveness of school management, due to the active involvement of teachers and education staff in program planning, implementation, and evaluation. Meanwhile, transparency and accountability have been implemented but tend to be administrative in nature and have not been optimally utilized in decision-making. Data integration shows that the effectiveness of school management is more influenced by active participation than by formal transparency and accountability. Therefore, improving the quality of participation is key to achieving effective school management.